2013
DOI: 10.1128/iai.00497-13
|View full text |Cite
|
Sign up to set email alerts
|

Perforin-2 Restricts Growth of Chlamydia trachomatis in Macrophages

Abstract: Chlamydia trachomatis is a Gram-negative obligate intracellular bacterium that preferentially infects epithelial cells. Professional phagocytes provide C. trachomatis only a limited ability to survive and are proficient killers of chlamydiae. We present evidence herein that identifies a novel host defense protein, perforin-2, that plays a significant role in the eradication of C. trachomatis during the infection of macrophages. Knockdown of perforin-2 in macrophages did not alter the invasion of host cells but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 49 publications
(46 reference statements)
4
52
0
Order By: Relevance
“…Shield-1-sensitive fusion proteins offered unparalleled posttranslational control over a particular substrate; however, they are model proteins, and it is unknown whether Chlamydia infections happen to target elements of these fusion proteins or DRiPs in general. While in vitro experiments have demonstrated that cells of hematopoietic origin, such as dendritic cells and macrophages (42,43), can be infected with different Chlamydia species, epithelial cells are the primary target of infections in vivo and antigenic peptides derived from DRiPs are present in different amounts depending on the cell type (44). However, the phenomenon is not limited to JY cells, since an epithelial cell line transiently transfected with SCRAP-SVG also increased DRiP presentation, while stable protein accumulation was diminished (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Shield-1-sensitive fusion proteins offered unparalleled posttranslational control over a particular substrate; however, they are model proteins, and it is unknown whether Chlamydia infections happen to target elements of these fusion proteins or DRiPs in general. While in vitro experiments have demonstrated that cells of hematopoietic origin, such as dendritic cells and macrophages (42,43), can be infected with different Chlamydia species, epithelial cells are the primary target of infections in vivo and antigenic peptides derived from DRiPs are present in different amounts depending on the cell type (44). However, the phenomenon is not limited to JY cells, since an epithelial cell line transiently transfected with SCRAP-SVG also increased DRiP presentation, while stable protein accumulation was diminished (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In cell-based infection studies, the proliferation of a number of intracellular bacterial pathogens is greatly enhanced when cellular Perforin-2 levels are reduced, suggesting that Perforin-2 targets vacuole-and plasma membrane-bound bacteria (15). Additionally, at least one intracellular pathogen, Chlamydia trachomatis, has evolved to actively block inductive Perforin-2 expression in epithelial cells (16). Thus, it appears that while Perforin-2 targets intracellular bacteria, it also can be targeted itself by pathogens in order to enhance their intracellular replication.…”
mentioning
confidence: 99%
“…We have recently shown that the mammalian MPEG1 homolog is constitutively expressed in macrophages, whereas in fibroblast-and endothelium-derived cells its expression is induced by interferons as well as infection with intracellular bacterial pathogens (15,16). In mice and humans the MPEG1 gene product, which is designated Perforin-2, is a 72-kDa protein possessing an MACPF domain in addition to a putative transmembrane and cytosolic domains.…”
mentioning
confidence: 99%
“…Intracellular bacterial killing assays were performed as previously described (2,9). Briefly, cells were infected with M. avium or S. aureus for 1 hour or S. typhimurium for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, all cells have the ability to express MPEG1, including barrier cells, such as keratinocytes and mucosal epithelium, and parenchymal cells (2,6). Perforin-2 has been shown to play a role in antibacterial defense in both invertebrate organisms, such as the disk abalone, and in vertebrates such as zebrafish, mouse, and human cells (2,(7)(8)(9). Murine macrophages and embryonic fibroblasts restrict intracellular bacterial growth through the agency of perforin-2 (2, 6, 9), whereas Mpeg1…”
Section: Introductionmentioning
confidence: 99%